2017
DOI: 10.7567/apex.10.071003
|View full text |Cite
|
Sign up to set email alerts
|

Polychromatic emission from polar-plane-free faceted InGaN quantum wells with high radiative recombination probabilities

Abstract: We fabricated three-dimensional (3D) InGaN quantum wells (QWs) on semipolar GaN substrates by selective area epitaxy. It was found that polar-plane-free 3D structures can be fabricated with a particular mask pattern on the plane and that InGaN/GaN QWs on these structures exhibit facet-dependent polychromatic emission properties. In addition, time-resolved photoluminescence spectroscopy indicated that the radiative recombination lifetimes of the obtained 3D QWs without the polar (0001) plane are much shorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…2(d)] disappears where the surface is disturbed. The arms of the chevron appear to have a different semi-polar orientation, and therefore are expected to have a different rate of InN incorporation, [29][30][31] than the majority of the sample, which could account for this considerable redshift. A similar shift has been seen in chevrons for samples with comparable emission energy in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…2(d)] disappears where the surface is disturbed. The arms of the chevron appear to have a different semi-polar orientation, and therefore are expected to have a different rate of InN incorporation, [29][30][31] than the majority of the sample, which could account for this considerable redshift. A similar shift has been seen in chevrons for samples with comparable emission energy in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding details of the growth conditions were described in Refs. [2] and [9]. The QW local structural properties were assessed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy (EDS).…”
Section: Methodsmentioning
confidence: 99%
“…In composition) has been attributed to active In adatom migration from the inclined {1122} to top (0001) facets [10]. In contrast, the emission wavelengths from the 3D QWs on (1122) are in the order of inclined {1101} > top (1122) > side {1100} [9]. Because both 3D QWs have similar trapezoidal cross sections, the observed difference indicates the presence of an unknown factor in addition to adatom migration.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been reported that the indium incorporation rate at the front edge (20-21) of the arrowhead-like structure is higher than the sidewall edge (10)(11) and upper plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) regions. [24][25][26] As the HP-ELO GaN template with a width of 9.0 μm has the maximum area of a large and small arrowhead-like buddle structures, the density of front edge, which can have a high indium composition region, is maximized at the 9.0 μm-width hexagonal pattern shown in Figure 2d. Therefore, we believe that the highest indium localization and longest emission wavelength were obtained by the HP-ELO GaN-based LED with a width of 9.0 μm.…”
Section: Spectral Behaviors Of Hp-elo Gan-based Leds With Different Hmentioning
confidence: 99%
“…Based on these results, we believe that the indium incorporation rate decreases in the order of the front edge (20)(21), side edge (10)(11), and top plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) of the arrowhead-like surface structure. [24][25][26] 3.4. Injection Current Controlled Red, Green and Blue Emissions of Semipolar HP-ELO GaN-Based LEDs Figure 6 shows the EL spectra of a semipolar (11-22) HP-ELO GaN-based LEDs with a 9.0 μm-width hexagonal pattern as the injection current is increased from 0.01 to 5.0 mA.…”
Section: Strong Blueshifts Of Hp-elo Gan-based Leds Withmentioning
confidence: 99%